(untitled) (Plant Tissue Culture and Biotechnology, 2022)
This study was undertaken to evaluate the removal of lipid-rich organic matter from wastewater by lipase producing bacteria. Ten potential lipase producing bacteria were isolated from lipid-rich environments in and around Dhaka Metropolitan city. Three of them produced lipase higher than 10 U/ml. These three isolates and their consortium were used for synthetic wastewater treatment in the laboratory. The initial COD value of synthetic wastewater was 1,200 mg/l. COD removal efficiencies in the synthetic wastewater were 74.75, 73.33 and 66.67% by the Stenotrophomonas maltophilia e-a22, Pseudomonas aeruginosa 12 and Bacillus subtilis 20B, respectively. Stenotrophomonas maltophilia showed better COD removal performance (74.75%) in case of monoculture. But consortium showed better COD removal (83.33%) than that of monoculture. Therefore, it could be concluded that consortium of three isolates will be more useful for wastewater treatment as seed cultures in the wastewater treatment plant associated with the lipid-rich wastewater. Plant Tissue Cult. & Biotech. 31(2): 135-142, 2021 (December)